Exploring the relationship between agribusiness investments and postharvest losses among smallholder vegetable farmers in the eThekwini Municipality - Qange, Siphesihle; Mdoda, Lelethu; Mditshwa, Asanda (Frontiers in Sustainable Food Systems, 2024)
Smallholder vegetable farmers in developing economies play a crucial role in agricultural production but often face significant postharvest losses at various stages of the value chain. Agribusiness investments have the potential to address postharvest losses for smallholder vegetable farmers. Understanding the impact of these investments is crucial due to their potential benefits. Therefore, this study aims to explore the relationship between agribusiness investments and postharvest losses among smallholder vegetable farmers, in eThekwini Municipality. Using structured questionnaires, a cross-sectional research design and a multi-stratified random sampling technique were employed to collect primary data from 238 farmers. The study used descriptive statistics and ordinary least square regression to analyse the data. The study results revealed that the majority (56%) of the farmers were females with an average age of 45 years and a household size of 5 people per household. Farmers spent an average of 12 years in school, with the majority being unemployed (76%) and relying on farming for income (78%). Moreover, the study revealed that 90% of the farmers lose their produce due to less demand, while 88% believe that the cost of inputs affects them. Additionally, 79% of the farmers believe that high competition in the market results in postharvest losses, and 70 and 69% indicate that weather conditions and adoption of farming practices, respectively, influence their postharvest losses. The Ordinary Least Squares regression model results indicated that agribusiness investments, transport infrastructure, financial support, market demand, weather conditions, adoption of new technologies, and market access significantly influence postharvest losses among smallholder vegetable farmers in the eThekwini Municipality. The study, therefore, recommends investing in transportation infrastructure, promoting climate-resilient agriculture, facilitating market access, providing financial support, and urgently strengthening extension services to reduce postharvest losses in the agricultural sector. The need for strengthening extension services is particularly urgent, as it can provide farmers with the necessary knowledge and skills to adopt new technologies and farming practices, thereby reducing postharvest losses.